2022
DOI: 10.1186/s13018-022-03227-w
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of non-operative treatment of patients with knee arthrofibrosis using high-intensity home mechanical therapy: a retrospective review of 11,000+ patients

Abstract: Background Recovery from knee surgery or injury can be hindered by knee arthrofibrosis, which can lead to motion limitations, pain and delayed recovery. Surgery or prolonged physical therapy are often treatment options for arthrofibrosis, but they can result in increased costs and decreased quality of life. A treatment option that can regain lost motion without surgery would help minimize risks and costs for the patient. The purpose of this study was to determine treatment efficacy of high-inte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(10 citation statements)
references
References 38 publications
0
10
0
Order By: Relevance
“…A recent study revealed that high-intensity home mechanical stretch therapy effectively restored knee flexion within two months or less. 76 This approach was shown to prevent additional surgery and minimize emotional distress, irrespective of sex, age, or worker's compensation status. 76 The authors recommended a high-intensity stretching program for any patient at risk of secondary motion loss after surgery.…”
Section: Nonsurgical Managementmentioning
confidence: 99%
See 1 more Smart Citation
“…A recent study revealed that high-intensity home mechanical stretch therapy effectively restored knee flexion within two months or less. 76 This approach was shown to prevent additional surgery and minimize emotional distress, irrespective of sex, age, or worker's compensation status. 76 The authors recommended a high-intensity stretching program for any patient at risk of secondary motion loss after surgery.…”
Section: Nonsurgical Managementmentioning
confidence: 99%
“…76 This approach was shown to prevent additional surgery and minimize emotional distress, irrespective of sex, age, or worker's compensation status. 76 The authors recommended a high-intensity stretching program for any patient at risk of secondary motion loss after surgery. The 6-10 week program provided an average of > 25 o of flexion gain.…”
Section: Nonsurgical Managementmentioning
confidence: 99%
“…19 Pain, delayed recovery, and motion limitations are all symptoms of arthrofibrosis post-ligamentous surgery that can significantly affect the livelihoods of patients and not only prevent them from work, but also create financial stress. 3 Even a small loss of knee extension, such as 5°, can debilitate a patient from walking normally and loss of flexion can create issues with climbing stairs, sleeping, driving, and getting in and out of chairs. 5 The inability to do these simple everyday tasks can significantly affect patients' careers, resulting in job loss in severe cases.…”
Section: Livelihoods and Jobsmentioning
confidence: 99%
“…2 There are an estimated 85,000 patients who develop postoperative knee arthrofibrosis in the United States per year. 3 The rate of reported incidence of arthrofibrosis following ACL reconstruction ranges from 4% to 38%. 4 The types of surgeries and the percentage of patients that have continued severe motion loss beyond 1 year after that surgery (in parentheses) include anterior cruciate ligament (ACL) reconstruction (2-35%), multiple ligament reconstruction (13-22.4%), total knee arthroplasty (1.3-12%), tibial plateau fracture repair (14.5%), and femur fracture repair (29.5%).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation